2019
DOI: 10.1016/j.scitotenv.2019.05.371
|View full text |Cite
|
Sign up to set email alerts
|

Return flows from beaver ponds enhance floodplain-to-river metals exchange in alluvial mountain catchments

Abstract: River to floodplain hydrologic connectivity is strongly enhanced by beaver-(Castor canadensis) engineered channel water diversions. The hydroecological impacts are wide ranging and generally positive, however, the hydrogeochemical characteristics of beaver-induced flowpaths have not been thoroughly examined. Using a suite of complementary ground-and drone-based heat tracing and remote sensing methodology we characterized the physical template of beaver-induced floodplain exchange for two alluvial mountain stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Our selected field study highlights one specific application of CC, being a rapid, noninvasive technology for identifying anoxic groundwater discharge zones resulting in high concentrations of Fe(III) oxides, especially when Fe(III) oxides are not visible due to deep or turbid water, aquatic vegetation, or shallow burial. These discharge zones can occur frequently when the groundwater is impacted by anthropogenic contamination such as landfill leachate (Bakyayita et al., 2019) and mining activities (Gandy et al., 2007) or natural processes such as beaver activity (Briggs et al., 2019) and organic‐rich peat deposits (Briggs et al., 2018b). Those processes consume the groundwater dissolved oxygen and increase the dissolved ions either by direct inputs or reducing the aquifer geological minerals, which result in unique discharge zones considered as hotspots for biogeochemical reactions (Boano et al., 2014; Vidon et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our selected field study highlights one specific application of CC, being a rapid, noninvasive technology for identifying anoxic groundwater discharge zones resulting in high concentrations of Fe(III) oxides, especially when Fe(III) oxides are not visible due to deep or turbid water, aquatic vegetation, or shallow burial. These discharge zones can occur frequently when the groundwater is impacted by anthropogenic contamination such as landfill leachate (Bakyayita et al., 2019) and mining activities (Gandy et al., 2007) or natural processes such as beaver activity (Briggs et al., 2019) and organic‐rich peat deposits (Briggs et al., 2018b). Those processes consume the groundwater dissolved oxygen and increase the dissolved ions either by direct inputs or reducing the aquifer geological minerals, which result in unique discharge zones considered as hotspots for biogeochemical reactions (Boano et al., 2014; Vidon et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In an additional application of CC measurements to a zone of known anoxic floodplain seepage along the larger alluvial East River (Colorado, USA), we found a similar correlation between italicσsed and evidence of Fe(III) oxide precipitates to that observed in the Mashpee River. In East River, anoxic groundwater discharges were induced by floodplain beaver pond subsurface return flows, which produced visible rust‐stained sediments indicating Fe(III) oxide precipitates (Briggs et al., 2019) (Figure ). Distinctly higher italicσsed (at 4 Hz) was acquired over these rust‐stained sediments (2.3 ± 0.77 μS cm −1 from 22 different sites) relative to the more typically alluvial sediments along the main river channel (0.26 ± 0.37 μS cm −1 from 14 different sites) (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulative effects of these expanded pathways are not well known in beaver systems, but it is nonetheless a mechanism to increase the concentration of Fe 3+ and associated metals and nutrients in solution, which may then in turn be re-oxidised by a variety of abiotic and biological mechanisms if these pathways re-enter downstream anaerobic surface waters (Figure 15). Indeed, Briggs et al (2019) found that beaver dam induced diversion of water across a floodplain resulted in subsequent return flow to the main channel that was variable in redox status and substantially enriched in iron, manganese, aluminium, and arsenic concentrations. Some combination of expanded anaerobic conditions and flow mixing may thus lead to the enhancement of Fe 2+ concentrations downstream of beaver systems, which Cirmo and Driscoll (1993) found could be up to four times higher than inflowing concentrations.…”
Section: Impacts On Iron Cycling Mercury and Additional Contaminantsmentioning
confidence: 99%